Identification of dynamic RNA-binding proteins uncovers a Cpeb4-controlled regulatory cascade during pathological cell growth of cardiomyocytes - Riechert, Eva; Kmietczyk, Vivien; Stein, Frank; Schwarzl, Thomas; Sekaran, Thileepan; Jürgensen, Lonny; Kamuf-Schenk, Verena; Varma, Eshita; Sandmann, Christoph; Rettel, Mandy; Gür, Kira; Ölschläger, Julie; et al. (Cell reports, 2021)
RNA-binding proteins (RBPs) control critical aspects of cardiomyocyte function, but the repertoire of active RBPs in cardiomyocytes during the growth response is largely unknown. We define RBPs in healthy and diseased cardiomyocytes at a system-wide level by RNA interactome capture. This identifies 67 cardiomyocyte-specific RBPs, including several contractile proteins. Furthermore, we identify the cytoplasmic polyadenylation element-binding protein 4 (Cpeb4) as a dynamic RBP, regulating cardiac growth both in vitro and in vivo. We identify mRNAs bound to and regulated by Cpeb4 in cardiomyocytes. Cpeb4 regulates cardiac remodeling by differential expression of transcription factors. Among Cpeb4 target mRNAs, two zinc finger transcription factors (Zeb1 and Zbtb20) are discovered. We show that Cpeb4 regulates the expression of these mRNAs and that Cpeb4 depletion increases their expression. Thus, Cpeb4 emerges as a critical regulator of cardiomyocyte function by differential binding to specific mRNAs in response to pathological growth stimulation.